A comparative evaluation of 'Hass' type avocado cultivars on postharvest pericarp colour development and correlation with softening : a case of 'Hass', 'Maluma- Hass' and 'Carmen-Hass' - Ledwaba, Kagisho Florence (My University, 2025)
During ripening, 'Hass' avocado fruit change colour from green to purple/black. However, early-season fruit exhibit a poor colour development, and this issue has not been studied in 'Carmen-Hass' and 'Maluma-Hass' when compared with traditional ‘Hass’ fruit. Therefore, the objective of this study was to compare the postharvest exocarp colour change for 'Carmen-Hass' and 'Maluma-Hass' avocado with 'Hass' and evaluate their correlation with fruit softening. The early-season fruit were harvested from a commercial farm, thereafter transported to the laboratory for further storage and analysis. At harvest, avocado fruit were assessed for dry matter content, whereas visual and objective colour parameters, firmness, and chilling injury were assessed during 12 days of ripening. The results showed that 'Carmen-Hass' avocado fruit exhibited the highest dry matter content at harvest when compared with 'Hass' and 'Maluma-Hass' cultivars. Furthermore, 'Carmen-Hass' fruit showed the highest visual colour change during ripening, followed by 'Maluma-Hass' after 12 days of ripening. All cultivars exhibited a decrease in lightness (L*) values throughout the ripening period, with 'Carmen-Hass' showing the most pronounced change between days 2 and 4 of ripening. A decrease in chroma (C*) values was observed across all cultivars throughout the ripening period, with 'Maluma-Hass' displaying the lowest C* values from day 8 to 12. There was a notable decrease in hue angle (h°) for all the cultivars throughout the ripening period, with 'Maluma-Hass' showing the most significant decrease from days 6 to 8. With respect to firmness, the three cultivars showed a decrease in firmness during ripening indicating that 'Carmen-Hass' softened the quickest, followed by 'Hass', while 'Maluma-Hass' retained firmness the longest. The 'Carmen-Hass' cultivar exhibited the lowest chilling damage, followed by 'Maluma-Hass', while the highest chilling index was recorded on 'Hass' fruit. In 'Carmen-Hass', firmness was highly negatively correlated with visual colour (R= -0.942, p < 0.01) and greenness (R = -0.904, p < 0.001). There was also a highly positive correlation between firmness and peel colour lightness (R= 0.859, p < 0.001) and chroma (R= 0.79, p < 0.001) as compared with 'Hass ' and 'Maluma-Hass'. In conclusion, 'Carmen-Hass' showed improved colour (black) development during ripening when compared with 'Hass' and 'Maluma-Hass' fruit. The findings suggest that all ‘Hass’ type avocado cultivars ripen and their firmness decreases during storage. However, there was a significant difference in their exocarp colour change.
Thesis (M.Sc. (Horticulture)) -- University of Limpopo, 2025
Keywords: Hass' avocado; Carmen-Hass; Fruit; Maluma-Hass; Avocado -- Varieties; Avocado industry; Avocado -- Postharvest physiology